2017
DOI: 10.1111/bcpt.12919
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Cystatin C in HIV/AIDS Patients with Metabolic Syndrome

Abstract: Data about Cystatin-C levels in HIV-infected patients with metabolic syndrome (MetS) are still limited. Therefore, the aim of this study was to evaluate the possible correlations of serum levels of Cystatin-C in HIV/AIDS patients treated with combined antiretroviral therapy (cART) with or without MetS. This cross-sectional study included 89 HIV/AIDS Caucasian patients receiving cART at the HIV/AIDS Centre Belgrade, Serbia, divided into two groups according to the presence of MetS. Cystatin-C and other biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The combination of HIV infection with MetS seems to exacerbate the renal damage caused by the virus, with PLWH presenting a higher urinary albumin–creatinine ratio compared to non-HIV-infected patients with MetS [99]. Always related to renal damage, a correlation was found between levels of cystatin-C (a marker of kidney function recently shown to be associated with a risk of developing CVDs and DM) and MetS [100]. PLWH with MetS showed higher levels of aspartate transaminase, triglycerides, and blood pressure, and lower levels of cholesterol HDL compared to patients without MetS.…”
Section: Non-aids Co-morbidities In Plwhmentioning
confidence: 99%
“…The combination of HIV infection with MetS seems to exacerbate the renal damage caused by the virus, with PLWH presenting a higher urinary albumin–creatinine ratio compared to non-HIV-infected patients with MetS [99]. Always related to renal damage, a correlation was found between levels of cystatin-C (a marker of kidney function recently shown to be associated with a risk of developing CVDs and DM) and MetS [100]. PLWH with MetS showed higher levels of aspartate transaminase, triglycerides, and blood pressure, and lower levels of cholesterol HDL compared to patients without MetS.…”
Section: Non-aids Co-morbidities In Plwhmentioning
confidence: 99%
“…Several studies have shown elevated levels of cystatin C in HIV positive patients in recent times which confirm the current result. 19,20 In this study, there was no significant difference in the mean plasma uric acid level observed in the symptomatic HIV participants on long term ART when compared to symptomatic HIV participants on short term ART (p>0.05). This may mean that duration of ART does not affect uric acid level in HIV participants.…”
Section: Discussionmentioning
confidence: 53%
“…24 However, the present result is in contrast with the results of some other similar studies documenting significantly elevated creatinine levels in HIV participants and HIV participants on ART compared to control group. 11,[13][14][15][16][17][18][19][20][21][22][23][24][25] Creatinine is a non-protein nitrogenous compound that is produced by the breakdown of creatine in muscle. Creatinine is found in serum, plasma, and urine and is excreted glomerular filtration at a constant rate and in the same concentration as in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystatin C (Cys-C), a low–molecular-weight cysteine protease inhibitor involved in vascular extracellular matrix remodeling, 8 is an established biomarker of glomerular filtration 9 and early renal dysfunction 10 and is also a predictive marker of CVD. 11,12 In the present study, we sought to examine the association between MetS and the biochemical profiles of an adult Chinese cohort.…”
Section: Introductionmentioning
confidence: 99%